2021
DOI: 10.1002/jmv.27170
|View full text |Cite
|
Sign up to set email alerts
|

Association between cycle threshold (Ct) values and clinical and laboratory data in inpatients with COVID‐19 and asymptomatic health workers

Abstract: In‐house assays for the diagnosis of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) by quantitative reverse‐transcription polymerase chain reaction (qRT‐PCR), are feasible alternatives, particularly in developing countries. Cycle threshold (Ct) values obtained by qRT‐PCR were compared with clinical and laboratory data from saliva of inpatients with COVID‐19 and asymptomatic health workers (AHW) were studied. Saliva specimens from 58 inpatients confirmed by qRT‐PCR for SARS‐CoV‐2 using nasopharyng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 33 publications
1
11
0
1
Order By: Relevance
“…This may indicate that the nasopharyngeal or oropharyngeal SARS-CoV-2 lower C t value directly impacts organ function. Our results are consistent with earlier research that reported the correlation between C t value and markers of inflammation 32,40 . In a study conducted by Zheng et al, similar outcomes were seen.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This may indicate that the nasopharyngeal or oropharyngeal SARS-CoV-2 lower C t value directly impacts organ function. Our results are consistent with earlier research that reported the correlation between C t value and markers of inflammation 32,40 . In a study conducted by Zheng et al, similar outcomes were seen.…”
Section: Discussionsupporting
confidence: 94%
“…Indeed, serum ferritin is affected by hepcidin upregulation, which is stimulated by proinflammatory cytokines, particularly IL-6 31 . Ferritin is highly relevant because it is a mediator of immune dysregulation; it has been proposed that under extreme hyperferritinemia, Ferritin generates direct immunosuppressive and proinflammatory impacts, contributing to the cytokine storm shown in COVID patients 19 32 . Because hyperferritinemia causes regular cell death (RCD), iron oxides interact with serum coagulation cascade proteins.…”
Section: Discussionmentioning
confidence: 99%
“…In SARS‐CoV‐2‐infected patients, the association between initial C t value and patient age was not significant. The association between viral load expressed by the C t value and sample type, clinical/laboratory data, and disease severity has been previously reported 30,31 …”
Section: Discussionmentioning
confidence: 88%
“…The association between viral load expressed by the C t value and sample type, clinical/laboratory data, and disease severity has been previously reported. 30 , 31 …”
Section: Discussionmentioning
confidence: 99%
“…This was lower than the study by Senok A et al [11] where the sensitivity and specificity was 73.1 % and 97.6 % respectively. Connor et al [15] demonstrated a sensitivity of 85.3 % and Ramirez-Hinojosa et al [19] had a sensitivity of 87.9 %. However, neither reported specificity.…”
Section: Discussionmentioning
confidence: 99%